Credit Transactions of People from Cernica in Dubrovnik in the 15th Century - Pekić, Radmilo B. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Cernica was one of the most important settlements in the medieval Bosnia, whose development was encouraged by the caravan trade. Located on one of the major roads ‘Via Drine’ that caravans from Dubrovnik to Bosnia and Serbia went down, Cernica gradually turned from the caravan station into a square. Caravans that set off from Dubrovnik and followed the said road, Cernica was the first lap of their journey, where tradesmen and their pack animals took a rest. It has earlier been established that all kinds of facilities for the accommodation of tradesmen, goods and animals were constructed in the caravan stations. Gradually service, craftsmanship and commercial activities developed in Cernica and they influenced its development. The Gacko and Cernica Fields favoured the livestock farming and bee-keeping. Accordingly, livestock and its products and wax were the main exporting articles from Cernica.Depending on their proprietary state, the business people from Cernica went to Dubrovnik and purchased goods, mainly fabric in delayed payment. After a certain period they sold the fabric and other goods, and settled their debts both with money and other goods necessary on the Dubrovnik market. More than a thousand documents mentioning the medieval Cernica and its population were saved in the Dubrovnik archive. Based on the published and unpublished Dubrovnik sources, this article presents only a segment from the medieval history of the Cernica population and credit transactions in Dubrovnik in the 15th century, that represent a basis for further and more extensive investigation of this area.
Keywords: debts; trade; credit; Dubrovnik; Cernica